Designing an English for Academic Purposes (EAP) Model for Computer Science Students: A Case Study at an Indonesian Polytechnic Institution - Ismail, Mohamad Arif (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The limited implementation of English for Academic Purposes (EAP) courses in Indonesian vocational higher education highlights a critical gap, particularly for students of Computer Science. This study explores the design of an EAP syllabus tailored to the specific academic and professional needs of Computer Science students at Polytechnic Gorontalo, Indonesia. Grounded in established theories of EAP and needs analysis, including frameworks by Munby (1978), Hutchinson and Waters (1987), and Dudley-Evans and St John (1998), the research employed a mixed-methods approach, utilizing questionnaires and stakeholder interviews to investigate both target and learning needs. The findings reveal that students prioritize speaking skills, particularly in social interactions, oral presentations, and job interviews, followed by writing tasks related to advertising, academic work, and job applications. Reading and listening are also acknowledged as supporting skills for academic engagement. Based on these insights, a skills-based syllabus was developed, structured into thematic units across a semester, with performance-oriented assessment and both formative and summative evaluations. This study contributes to the discourse on localized EAP course design by offering a context-specific syllabus that addresses learners' communicative competence for academic and occupational success. The proposed model showcases originality in its integration of needs analysis with computer science content and underscores its applicability to vocational settings in similar EFL contexts. Keywords: EAP, Needs Analysis, Syllabus Design